可燃性ガス及び蒸気の平面型熱触媒センサー (2021)
The invention relates to gas analysis and to combustible gas and vapour analyzers based on a thermocatalytic operating principle. The subject of the invention is a sensor the sensitive elements of which are manufactured by planar techniques that can be easily automated. The main distinguishing feature is that a working sensitive element and a reference sensitive element are colocated in a single micron-sized structural component (a microchip) on a common substrate made of porous anodic aluminium oxide. The design of the sensitive elements provides for film-wise heat transfer from heated parts of the working and reference sensitive elements. Measuring microheaters which heat the working and reference sensitive elements up to working temperatures and provide for differentially measuring an output signal in a measuring bridge circuit are spaced apart at opposite sides of the anodic aluminium oxide substrate and are disposed on arms projecting beyond the common substrate configuration. The sensitive elements are disposed in a reaction chamber having restricted diffusion access via a calibrated orifice, and the diameter of regular pores in the microchip substrate is increased to sizes that provide for a predominantly molecular diffusion mode in the pores (100 nm or more).